2019
DOI: 10.1016/j.envpol.2019.06.121
|View full text |Cite
|
Sign up to set email alerts
|

Brominated and organophosphorus flame retardants in South African indoor dust and cat hair

Abstract: Flame retardants (FRs), such as brominated flame retardants (BFRs) and organophosphorus flame retardants (OPFRs), are diverse groups of compounds used in various products related to the indoor environment. In this study concentrations of eight polybrominated diphenyl ethers (PBDEs), two alternative BFRs and ten OPFRs were determined in indoor dust (n ¼ 20) and pet cat hair (n ¼ 11) from South Africa. The OPFRs were the major FRs, contributing to more than 97% of the total FR concentration. The median Ʃ 10 OPFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 52 publications
2
10
1
Order By: Relevance
“…A global air survey found that OPE level in air was significantly higher than that of PBDEs and other novel FRs . Studies conducted in North America, , Europe, and Africa also confirmed that the contamination of OPEs has surpassed that of BFRs in various matrices. In China, a study conducted in Guiyu, China showed that levels of OPEs in sediments were much higher than that of BFRs .…”
Section: Resultsmentioning
confidence: 91%
“…A global air survey found that OPE level in air was significantly higher than that of PBDEs and other novel FRs . Studies conducted in North America, , Europe, and Africa also confirmed that the contamination of OPEs has surpassed that of BFRs in various matrices. In China, a study conducted in Guiyu, China showed that levels of OPEs in sediments were much higher than that of BFRs .…”
Section: Resultsmentioning
confidence: 91%
“…House dust as a source of contaminants has been reported in the case of flame retardants, when a correlation was found between their concentration in house dust and cat hair or serum. 4850…”
Section: Discussionmentioning
confidence: 99%
“…As for several other SVOCs, levels of CPs in the indoor environment were higher than in the outdoors and varied with the types of buildings based on studies of both indoor and outdoor window films and air samples. , Concentrations of total CPs as high as mg/g have been reported for indoor dust from several countries worldwide (Table S1), , and CP concentrations exceeded those for the other flame retardants analyzed in the same dust samples. ,, Published data for CPs in indoor air (Table S1) are primarily only available for SCCPs and MCCPs, with only one reported study for vSCCPs, and none for LCCPs. There is a lack of data for CP concentrations in paired indoor air and indoor dust from the same microenvironment, and partitioning behavior of CPs between air and indoor dust thus remains unclear.…”
Section: Introductionmentioning
confidence: 99%